Antioxidant property and their free, soluble conjugate and insoluble-bound phenolic contents in selected beans. (June 2016) - Wang, Yu-Kun; Zhang, Xin; Chen, Guan-Lin; Yu, Jing; Yang, Lu-Qi; Gao, Yong-Qing
Highlights: Antioxidant capacities and total phenolic contents (free, esterified and insoluble-bound phenolics) of beans were evaluated. Gallic acid and protocatechuic acid were widely found in these beans. Findings of this study provide support for dietary guidelines and epidemiological research. Abstract: To explore the potential of common beans as natural sources of bioactive compounds, the antioxidant properties and total phenolic content (free, soluble conjugate, insoluble-bound fraction) of 14 beans from China were evaluated systematically. The results showed that beans had diverse antioxidant capacities and the variation was very large. Black bean, flower waist bean, pearl bean and spring bay bean showed the strongest antioxidant activities among the 14 tested samples based on a combinative consideration of the results obtained by 2, 2-diphenyl-1-picrylhydrazyl radical scavenging activity (DPPH) assay, ferric reducing antioxidant power (FRAP) assay, and trolox equivalent antioxidant capacity (TEAC) assay. Furthermore, several phenolic compounds were detected; gallic acid and protocatechuic acid were widely found in these beans. The results implied that these beans were important natural sources for preventing oxidative stress diseases.